2020
DOI: 10.17796/1053-4625-44.4.6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of New York Primary Care Physicians’ Knowledge, Attitudes, and Practices Related to Fluoride Varnish in an Urban Medical-Setting

Abstract: Objective: To determine changes in knowledge, attitudes, and practices of primary care physicians (PCPs) regarding fluoride varnish (FV). Study Design: Fifty-four PCPs at an urban medical center in New York completed a pre-intervention survey. A pediatric dental resident provided an hour-long educational lecture and a hands-on demonstration regarding FV application. Six months later, PCPs were sent a post-intervention survey via electronic mail. Results: Fifty-four PCPs participated in the pre-survey and FV tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…However, few PNPs were providing this service in the inpatient or outpatient medical settings. This finding is similar to published studies that assessed the provider type (physicians, family nurse practitioners, physician assistants, and PNPs) and patients with both public and private medical insurance (Kim et al, 2020; Kranz et al, 2022; Lian et al, 2020). Continued efforts are needed to increase pediatric primary care providers' delivery of fluoride varnish as well as emphasizing generalizability of oral health preventive practices and interventions to specialty clinics and intensive care/acute care settings.…”
Section: Discussionsupporting
confidence: 89%
“…However, few PNPs were providing this service in the inpatient or outpatient medical settings. This finding is similar to published studies that assessed the provider type (physicians, family nurse practitioners, physician assistants, and PNPs) and patients with both public and private medical insurance (Kim et al, 2020; Kranz et al, 2022; Lian et al, 2020). Continued efforts are needed to increase pediatric primary care providers' delivery of fluoride varnish as well as emphasizing generalizability of oral health preventive practices and interventions to specialty clinics and intensive care/acute care settings.…”
Section: Discussionsupporting
confidence: 89%
“…26 Previous research has found provider-reported barriers to the delivery of fluoride varnish include low payment rates, limited time, and insufficient training. [27][28][29] In a national study, fluoride varnish rates almost tripled in states with Medicaid payments at the 75th percentile versus the 25th percentile-an absolute difference of only $9 per application. 25 In addition to small differences in payments being associated with large differences in uptake, variation in prices paid by private insurers may additionally act as a barrier if it makes providers unsure of how much they will be reimbursed if they expand this service to their full patient panel.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the potential of fluoride varnish to help address oral health disparities, delivery of fluoride varnish during medical visits is low; fluoride varnish was included in only about 10% of medical visits paid by Medicaid 25 and only 5% of medical visits paid by private insurers in four New England states 26 . Previous research has found provider‐reported barriers to the delivery of fluoride varnish include low payment rates, limited time, and insufficient training 27–29 . In a national study, fluoride varnish rates almost tripled in states with Medicaid payments at the 75th percentile versus the 25th percentile—an absolute difference of only $9 per application 25 .…”
Section: Introductionmentioning
confidence: 99%
“…However, their clinical practice does not appear consistent with this favorable statement. According to various cross-sectional studies, 50 to 75% of physicians would not assess children’s risk for dental caries [ 25 , 26 ], more than 23% would not provide diet counseling [ 24 , 25 ], and less than 10% would apply fluoride varnish to high caries-risk children [ 26 – 28 ]. Considering dentists, studies also indicate that their daily practices do not strongly emphasize prevention.…”
Section: Introductionmentioning
confidence: 99%